CREATION AND INVESTIGATION OF PARAMETERS OF SEMICONDUCTOR DEVICES ON THE BASED AlAs-GaAs - FILMS - Antoschenko, V. S.; Baiganatova, Sh. B.; Taurbayev, T. I.; Frantsev, Yu. V. (Recent Contributions to Physics, 2009)
A cheap thin-film phototransducer with Аu/n - GaАs/n+ - GаАs/n – AlGaAs structure that was formed using a molten solution by the method of growth separation during liquid-phase epitaxy has been developed. Our obtained results show the adventage of application of sepation-film technology for developing devices in micro- and optoelectronics.